PENGARUH PERSEPSI KORUPSI PAJAK DAN KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KEPERCAYAAN OTORITAS PAJAK SEBAGAI VARIABLE MEDIASI - Silvia Imelda Cendrawinata; Sri Andriani (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
The research explores the effect of perceived tax corruption and the standard of tax services on taxpayer compliance, considering trust in tax authorities as a mediator. Indonesia continues to face challenges in achieving optimal tax compliance, despite its efforts to improve revenue collection. Negative public perceptions of tax corruption and inadequate service quality are identified as major barriers. Adopting a quantitative methodology, this study surveyed 48 individuals from the Kediri Young Entrepreneur (KYE) community. Questionnaires were used for data collection, which was then analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The findings show that tax corruption perception has a significant negative effect on taxpayer compliance, while tax service quality has a significant positive effect. Additionally, trust in tax authorities functions as an significant mediator connecting the independent variables to taxpayer compliance. This indicates that even in the presence of tax corruption perceptions, strong citizens’ trust in the taxation institution can enhance voluntary compliance. This paper extends the literature by integrating these three variables into a single empirical model, emphasizing the importance of a trust-based approach in tax administration. The practical implication suggests that government tax agencies should focus on service improvement and anti-corruption efforts to rebuild public trust and boost compliance behavior. This research offers valuable insights for policymakers seeking to increase sustainable tax compliance through improved service delivery and enhanced institutional integrity.